A record of porbeagle, Lamna nasus (Bonnaterre, 1788), in the Gulf of Trieste with discussion on its occurence in the Adriatic Sea - Lipej, Lovrenc; Uhan, Jernej; Mavrič, Borut; Vujčić-Karlo, Snježana (Institut za oceanografiju i ribarstvo, 2016)
A juvenile male of porbeagle (Lamna nasus) was caught in waters off Piran (Slovenia, northern Adriatic) on December 22, 2015. The specimen was accurately measured and weighed. Cephalopods and fish remains were found in its stomach contents. This is the first record of a porbeagle in the waters of Slovenia and in the Gulf of Trieste, and one of the few records up to date reported in the northern Adriatic Sea. The presence of this juvenile specimen arises a question whether the Adriatic Sea is a reproductive ground of this species. According to an older record from 1910, a female porbeagle with four embryos was caught on Ugljan Island, confirming the fact that porbeagles reproduced at least in the past in the Adriatic Sea.